Pulse-width modulation direct torque control induction motor drive with Kalman filter - Hau Huu Vo; Dung Quang Nguyen; Quang Thanh Nguyen; Chau Si Thien Dong; Thinh Cong Tran; Pavel Brandstetter (Universitas Ahmad Dahlan, 2021)
The paper deals with application of Kalman filter in induction motor drive using pulse-width modulation direct torque control (PWM-DTC). In the ﬁrst part, the conventional PWM-DTC drive is described and Kalman ﬁlter is utilized to filter components of stator current vector those are assumed to be disturbed by white noise. The second part contains simulation results that are obtained in different cases of load torque, process and measurement noise covariances. The integral time absolute error (ITAE) performance index, undershoot, ripple of important quantities are used to compare the conventional drive structure and proposed drive structure with Kalman filter. The simulation results confirm the expected dynamic response of the proposed structure.